Oxford international secondary science workbook grade 7 - Fullick, Ann (Karachi: Oxford University Press., 2024)
Oxford International Secondary Science Workbook for Grade 7 is a comprehensive resource designed to enhance and reinforce the concepts learned in the main textbook. This workbook includes a variety of exercises, practical activities, and review questions that encourage critical thinking and application of scientific principles across biology, chemistry, physics, and Earth sciences. Students are guided through hands-on experiments and investigations, fostering a deeper understanding of the material. With its focus on real-world applications and problem-solving skills, this workbook serves as an essential tool for students to solidify their knowledge and prepare for more advanced scientific studies.